Finding a Potential Bruceine D Inhibitor for Apoptotic Resistance Protein Pancreatic Cancer Based on Molecular Docking - Armi Wulanawati; Harry Noviardi; Muhamad Sholehuddin Malik Ibrohim (Universitas Gadjah Mada, 2018)
Pancreatic cancer arises when cells in the pancreas begin to multiply out of control. In pancreatic cancer, over expression of heat proteins (Hsp70, Hsp 90), constitutive activation of NFĸB, and Bcl-2 family are closely linked with resistance to apoptosis. Apoptotic resistance has been attributed to defects in apoptotic signaling pathways. Bruceine D, which found in abundance Brucea javanica, possesses potent anti-pancreatic cancer activity. In vitro result, bruceine D could induce apoptosis of pancreatic cancer cell. The aim of this study was to find the potential effect of bruceine D inhibitor on apoptotic resistance proteins in pancreatic cancer based on molecular docking. Docking showed a binding affinity between bruceine D with proteins involved in apoptosis using AutoDock. The results showed that free binding energy of Hsp70 is -5.19; Hsp90 -7.26; NFĸB1 -5.49; NFĸB2 -6.14; Bcl-W -6.02; Bcl-xL -5.45 kcal/mol. Based on the result, we conclude that bruceine D with Hsp90 protein has potential the best binding affinity than other proteins.